PTU-176 Systematic review with meta-analysis: prevalence of bile acid malabsorption in irritable bowel syndrome with diarrhoea. (22nd June 2015) - Slattery, S; Ford, AC; Aziz, Q; Farmer, AD
Abstract : Introduction: Irritable bowel syndrome is a prevalent disorder with a marked socioeconomic burden. Previous studies support the proposal that a subset of patients with features compatible with diarrhoea predominant IBS (IBS-D) have bile acid malabsorption (BAM). We aimed to perform a systematic review and meta-analysis to assess the prevalence of BAM in patients meeting accepted criteria for IBS-D. Method: MEDLINE and EMBASE were searched up to February 2015. Studies recruiting adults with IBS-D, defined either by the Manning, Kruis, Rome I, II or III criteria and which used 23-seleno-25-homotaurocholic acid (SeHCAT) testing for the assessment of BAM were included. BAM was defined as 7 day SeHCAT retention of <10%. We calculated the rate of BAM and 95% confidence intervals (CI) using a random effects model. The methodological quality of included studies was evaluated using the Quality Assessment for Diagnostic Accuracy Studies (QUADAS-2). Results: The search strategy identified 6 relevant studies comprising 908 individuals. The rate of BAM ranged from 16.9% to 35.3%, with an unadjusted rate of 29.3%. The pooled rate according to the random effect model was 28.1% (95% CI 22.6–34%), see Figure 1 . There was significant heterogeneity in effect sizes (Q-test X 2 = 17.9, p < 0.004; I 2 72.1%). The type of diagnostic criteria used or study country did not significantly modify the effect. Conclusion: These data provide evidence that in excess of one quarter of patients meeting accepted criteria for IBS-D have BAM. This distinction has implications for the interpretation of previous studies as well as contemporaneous clinical practice and future guideline development. Disclosure of interest: S. Slattery: None Declared, A. Ford: None Declared, Q. Aziz: None Declared, A. Farmer Speaker Bureau of: Almirall.